Co‐production with "vulnerable" groups: Balancing protection and participation. Issue 3 (6th December 2017) - Liabo, Kristin; Ingold, Anne; Roberts, Helen
Abstract: Background and aim: This paper explores the tension between participation and protection at a time when professionals are encouraged to engage patients and citizens in both the "R" (research) and the "D" (development) of services. Concerns to protect groups perceived as "vulnerable" can mean that not everyone is afforded the same opportunity to participate. Methods: Our data draw on the literature and secondary analysis of a study designed to explore the experiences of young peoples' transitions from health and social care to adult services. In seeking ethics approval, tensions between protection and participation were evident, and once the study was concluded, we reviewed group and individual interview transcripts, team email correspondence, and research notes. We considered aspects of participation, co‐production, involvement, and research design in relation to the ethics concerns raised. Findings: In terms of privacy and confidentiality, young people were skilled at setting their own boundaries. Whilst young people leaving foster and residential care are frequently perceived as vulnerable, those in our study asserted their agency and desire to be "visible." Some experienced conditions aimed at protecting their confidentiality or safety as oppressive. Conclusion: The risk reduction strategies that often underpin ethics approval processes can also carry risks. Limiting opportunities to play a part in research for people who may already be excluded on age, health, language, or other grounds reduces the range of lay knowledge on which we can draw, limits generalisability, and potentially adds to damaging social exclusion. Learning how to participate effectively is a life skill. Abstract : Young people leaving care are frequently perceived as vulnerable, but those in our study asserted their agency and desire to be 'visible'. The risk reduction strategies which often underpin ethics approval processes can also carry risks. Limiting opportunities to play a part in research for people who may already be excluded on age, health, language or other grounds reduces the range of lay knowledge on which we can draw, limits generalisability and potentially adds to damaging social exclusion.